Achievement of beam steering in terahertz band based on frequency‐scanning grating‐reflector antenna. Issue 3 (1st January 2014) - Li, Shichao; Li, Chao; Zhang, Xiaojuan; Fang, Guangyou
Abstract : A frequency‐scanning grating‐reflector antenna operating in the 0.2 THz band is proposed. The antenna system consists of a planar grating reflector, a thin lens and a feed horn placed at the focal point of the lens. The beam‐scanning property based on the frequency sweeping was analysed and optimised based on Floquet's theorem. A bilayer structure is introduced to improve the diffraction efficiency and to suppress the specular beam. The frequency‐controlled beam steering concept was verified by the quasi‐optical measurements in the 0.2 THz band. The measured scanning range is 13.55° over the frequency band 180–220 GHz. The specular beams are remarkably inhibited with the diffractive efficiency as high as over 89%. The presented antenna has the advantage of the convenience to be extended to a higher frequency with a high directivity.